2014
DOI: 10.12691/ajphr-2-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Waist Circumference Affect Lipid Parameters Negatively in Turkish Women

Abstract: Study Design:Obesity prevalence is incresing in Turkish population whose lipoprotein profile is characterised by low levels of HDL cholesterol. Our study aims to determine how obesity changes lipid profiles in Turkish women. Materials and Methods: We evaluated 2501 overweight and obese adult women. After systemic physical examination and some antropometric studies, blood samples have been analysed for lipid parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
3
5
0
2
Order By: Relevance
“…An important observation in these analyses was that HDL-C was negatively correlated to WC, a biomarker of visceral obesity, as well as to BMI. These correlations have been reported by other investigators in heterogeneous populations [ 42 , 43 , 44 , 45 ]. This relationship between WC and HDL-C concentrations can be explained by the changes in fat depots which have an important impact in lipoprotein metabolism [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…An important observation in these analyses was that HDL-C was negatively correlated to WC, a biomarker of visceral obesity, as well as to BMI. These correlations have been reported by other investigators in heterogeneous populations [ 42 , 43 , 44 , 45 ]. This relationship between WC and HDL-C concentrations can be explained by the changes in fat depots which have an important impact in lipoprotein metabolism [ 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies support our results and have shown that visceral fat is correlated with metabolic risk factors including a reduction in HDLC as well as an increase in TG and insulin resistance, but not with abdominal subcutaneous fat. 15 16) Many studies have also reported a positive correlation between the TG/HDLC ratio and waist circumference; 17 18 19) however, the correlation between the TG/HDLC ratio and BMI has been inconsistent. 18 19 20) …”
Section: Discussionmentioning
confidence: 99%
“…The same observation was found with TG, LDL, and VLDL, whereas the HDL level was low in both groups with no significant differences. It is known that total cholesterol levels higher than 170 mg/dL and LDL-C levels higher than 110 mg/dL are high risk factors for many diseases [54]. Thus, diet may be responsible for the nonsignificance between the obese and non-obese groups in all lipid parameters.…”
Section: Resultsmentioning
confidence: 99%